Implementasi Program Mujawwad dalam Peningkatkan Kefasihan Membaca Al-Quran Siswa MTs PAB 1 Helvetia - Nabila Syafinka Putri; Abd Rahman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out how the mujawwad program is implemented at MTs PAB 1 Helvetia. This research uses qualitative research. Data collection techniques in this research are interviews, observation and documentation. The subjects of this research were school principals, PKS 3 student affairs teachers, special teachers who taught mujawwad. The data analysis techniques used are data collection, data reduction, data display, and veryfying. The results of this research show that the mujawwad program at MTs PAB 1 Helvetia is carried out on Mondays, Thursdays and Fridays. Outside school hours from 14.00 WIB to 15.00 WIB. This program aims to make students closer to the Al-Qur'an and love the Al-Quran, develop talents and excel in MTQ at the City/Regency level. The method in the mujawwad program at MTs PAB 1 Helvetia uses several methods, namely, 1. lecture method by providing material about the science of recitation. 2. demonstration method by modeling Al-Qur'an songs to students, then students follow the Al-Qur'an songs/maqam that have been taught by the teacher. 3. Iqra method for students who do not understand the science of recitation and maqam songs and cannot read the Al-Qur'an fluently. The process of implementing the mujawwad program at MTs PAB 1 Helvetia first tests the students who register to take part in the mujawwad program activities, after that they provide material about the science of recitation and maqam of the Koran, for students who are not yet fluent in reading the Al-Qur'an are required to bring an iqra to facilitate reading and improve recitation. The supporting factors in this program are adequate facilities and infrastructure, the methods taught to students can be understood well, and the teachers who teach in this program are the best Qori at national level. The inhibiting factors are the very short time, parents of students who do not allow it because the program is held outside school hours, students who are inconsistent in participating in the Koran recitation program at MTs PAB 1 Helvetia.